Molecular Diagnosis of Mycobacterium tuberculosis in paraffin-embedded pleural biopsies - Barrón, Helí (2006)
Objective: To determine the sensitivity of the test tuberculosis polymerase chain reaction (TB-PCR) compared to fluorochrome auramine “O” staining in histological embedded tissues of pleural biopsy in diagnosis of pleural tuberculosis. Materials and Methods: We used 48 formalin-fixed paraffin-embedded tissue obtained from the archives of the Department of Pathology, Hospital San Jose del Callao, and Instituto Nacional de Enfermedades Neoplasicas. Thirty cases had clinical diagnosis of tuberculosis and 18 different diagnosis. Results: Twenty-nine of 30 cases having tuberculosis were TB-PCR positive. All 18 negative cases were TB-PCR negative. The sensibility and the negative predictive value of TBPCR were 96,7% and 94,7% respectively. On the other hand, the sensitivity and negative predictive value of AFB-Auramine were 58,6% and 56,7%. The positive predictive value was 100% in both cases. Conclusion: TB-PCR is a very sensitive method for TB diagnosis in formalin-fixed, paraffin embedded pleural biopsies.